Active Turnover of Heme in Hibernation Period in Mammals - Lee, Phil Jun; Cho, Namki; Yoo, Hee Min; Kim, Hong Pyo (Frontiers in Physiology, 2020)
Heme oxygenase (HO)-1 plays an important role during hibernation by catalyzing the degradation of heme to biliverdin/bilirubin, ferrous iron, and carbon monoxide, which activates the protective mechanisms against stress. In this context, although it is important to analyze the metabolic processes of heme, to date, no study has approached. Therefore, our study aims to understand the process of heme biosynthesis, which regulates cell survival in conditions of hypothermia and calorie restriction (CR). During hibernation, the mRNA levels of enzymes responsible for de novo heme biosynthesis were increased in the liver tissue of a Syrian hamster model of hibernation. Moreover, heme trafficking and iron metabolism were found to be more active, as assessed based on the changes in the levels of heme transporter and ferroportin mRNA. The levels of HO-1, a powerful antioxidant, were also upregulated during hibernation. Additionally, increased levels of Sirt-1 mRNA were also observed. These enzymes are known to act as cellular metabolic sensors that activate the cytoprotective mechanisms. These results indicate that HO-1 induction, brought about by the upregulation of heme during the pre-hibernation period, may protect against external stress. Here, we describe heme catabolism during hibernation by analyzing the regulation of the key molecular players involved in heme metabolism. Therefore, this study offers a new strategy for the better regulation of intracellular heme concentrations during hypothermia and other stresses.